K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

3 tháng 8 2015

Bài 1 :

\(x^2-6x+8=x^2-2x-4x+8=x\left(x-2\right)-4\left(x-2\right)=\left(x-4\right)\left(x-2\right)\)

Bài 2 :

 \(x^8+x^7+1=x^8+x^7+x^6+x^5+x^4+x^3+x^2+x+1-x^6-x^5-x^4-x^3-x^2-x\)

\(=x^6\left(x^2+x+1\right)+x^3\left(x^2+x+1\right)+x^2+x+1-x^4\left(x^2+x+1\right)-x\left(x^2+x+1\right)\)

=\(\left(x^2+x+1\right)\left(x^6+x^3+1-x^4-x\right)\)

Tick đúng nha 

1 tháng 8 2021

X^2-6+8

1 tháng 6 2018

Ta có :

x7 + x5 + 1 

= x7 + x6 - x6 + 2x5 - x5 + x4 - x4 + x3 - x3 + x2 - x2 +1

= x2 . ( x5 - x4 + x3 - x + 1 ) + x . ( x5 - x4 + x3 - x + 1 ) + ( x5 - x4 + x3 - x + 1 )

= ( x2 + x + 1 )( x5 - x4 + x3 - x + 1 )

3 tháng 10 2016

Ta có :

\(x^8+x^7+1\)

\(=\left(x^8+x^7+x^6\right)-x^6+1\)

\(=x^6\left(x^2+x+1\right)-\left[\left(x^3\right)^2-1^2\right]\)

\(=x^6\left(x^2+x+1\right)-\left(x^3-1\right)\left(x^3+1\right)\)

\(=x^6\left(x^2+x+1\right)-\left(x^3+1\right)\left(x-1\right)\left(x^2+x+1\right)\)

\(=\left(x^2+x+1\right)\left[x^6-\left(x^3+1\right)\left(x-1\right)\right]\)

\(=\left(x^2+x+1\right)\left[x^6-\left(x^4-x^3+x-1\right)\right]\)

\(=\left(x^2+x+1\right)\left(x^6-x^4+x^3-x+1\right)\)

1 tháng 6 2018

Ta có :

x7 + x2 + 1 = x7 - x + x2 + x + 1

= x . ( x3 + 1 ) . ( x3 - 1 ) + ( x2 + x + 1 )

= x . ( x3 + 1 ) . ( x - 1 ) . ( x2 + x + 1 ) + ( x2 + x + 1 ) 

= ( x2 + x + 1 ) ( x5 - x+ x2 - x + 1 )

20 tháng 8 2015

 x7 + x2 + 1 = (x7 – x) + (x2 + x + 1) 
= x.(x6 – 1) + (x2 + x +1) 
= x.(x3 - 1).(x3 +1) + (x2 + x +1) 
= x.(x-1).(x2 + x +1).(x3 +1) + (x2+ x +1) 
= (x2 + x +1).[x.(x-1).(x3 +1) + 1] 
= (x2 + x +1).[(x2-x).(x3 +1) + 1] 
= (x2 + x +1).(x5-x4 + x2 -x + 1)

17 tháng 9 2017

x7 + x2 + 1 = (x7 – x) + (x2 + x + 1) 
= x.(x6 – 1) + (x2 + x +1) 
= x.(x3 - 1).(x3 +1) + (x2 + x +1) 
= x.(x-1).(x2 + x +1).(x3 +1) + (x2 + x +1) 
= (x2 + x +1).[x.(x-1).(x3 +1) + 1] 
= (x2 + x +1).[(x2-x).(x3 +1) + 1] 
= (x2 + x +1).(x5-x4 + x2 -x + 1)

16 tháng 8 2015

\(=x^8-x^6+x^5-x^3+x^2+x^7-x^5+x^4-x^2+x+x^6-x^4+x^3-x+1\)

\(=x^2\left(x^6-x^4+x^3-x+1\right)+x\left(x^6+x^4+x^3-x+1\right)+\left(x^6-x^4+x^3-x+1\right)\)

\(=\left(x^2+x+1\right)\left(x^6-x^4+x^3-x+1\right)\)

phù !!!!!